2022
DOI: 10.1016/j.mcpro.2021.100185
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine-Fructose-6-Phosphate Transaminase 2 (GFPT2) Is Upregulated in Breast Epithelial–Mesenchymal Transition and Responds to Oxidative Stress

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 113 publications
(113 reference statements)
1
14
0
Order By: Relevance
“…Accuracy and validity of the proteomic analysis. The accuracy and validity of the proteomic analysis in this study were confirmed by comparing the current data to our previously generated proteomic data for the D492 EMT model [26]. The correlation between these two datasets was 0.936.…”
Section: Supporting Informationsupporting
confidence: 72%
See 4 more Smart Citations
“…Accuracy and validity of the proteomic analysis. The accuracy and validity of the proteomic analysis in this study were confirmed by comparing the current data to our previously generated proteomic data for the D492 EMT model [26]. The correlation between these two datasets was 0.936.…”
Section: Supporting Informationsupporting
confidence: 72%
“…(E) The RNA level of UGDH in all EMT models was consistently higher in the mesenchymal cell lines. (F) The UGDH protein level in the epithelial and mesenchymal cells was confirmed in another data set [ 26 ] and further confirmed in another tumorigenic breast mesenchymal cell line D492HER2. Student's t ‐test, * P < 0.05; ** P < 0.01; *** P < 0.001; n = 3.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations